(untitled) - Brinkley, Captain F. (Boston, 1902)
This book introduce about preconventional period ò foreign intercourse and trade. The propaganda and Chinese religions, conventional period, education, literati, secret societies, and rebellions. The second ửa and the events preceding.
Keywords: Trung Quốc,China; Lịch sử,History